2002
DOI: 10.1590/s0037-86822002000600013
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antifúngica de Caryocar brasiliensis (Caryocaraceae) sobre Cryptococcus neoformans

Abstract: The widespread occurrence of cryptococcosis mainly in immunocompromised patients and the side effects of available drugs which are effective against this mycosis have led investigators to search for new antimycotic agents. Caryocar brasiliensis derived compounds were investigated against Cryptococcus neoformans using the agar dilution method. Based on MIC values, the best results were obtained with a concentration of < 250 g/mL of cuticular waxes of the Caryocar brasiliensis leaf collected during the dry perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
15

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 14 publications
0
19
0
15
Order By: Relevance
“…Leaves infusion has been used for liver disorders (Siqueira, 1982). Molluscicidal activity of the crude extract against Biomphalaria glabrata , trypanosomicidal activity of the ethanol extract against Trypanosoma cruzi (Herzog-Soares, 2002) and antifungal activity of the oil (Passos et al, 2002) have also been reported. Its oleanolic acid has shown ability to inhibit the growth of mouse sarcoma 180 (Oliveira et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves infusion has been used for liver disorders (Siqueira, 1982). Molluscicidal activity of the crude extract against Biomphalaria glabrata , trypanosomicidal activity of the ethanol extract against Trypanosoma cruzi (Herzog-Soares, 2002) and antifungal activity of the oil (Passos et al, 2002) have also been reported. Its oleanolic acid has shown ability to inhibit the growth of mouse sarcoma 180 (Oliveira et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…PASSOS et al 68 have studied "in vitro" the antifungal activity of a plant extract against the yeast. Meningeal cryptococcosis-associated AIDS treatment is done in two phases: the first one in the acute or induction phase, for six to 10 weeks or until CFS becomes sterile.…”
mentioning
confidence: 99%
“…A planta toda é depurativa, anti-diarréica, purificadora, anti-reumática e para diminuir o colesterol do sangue (Pavan et al, 2009). …”
Section: Gabirobaunclassified
“…Bolsa-de-pastor A casca da raiz é utilizada para tratar afecções da pele e a casca do caule é antissifilítica (Rodrigues & Carvalho, 2001 (Passos et al, 2002).…”
Section: Zeyheria Montanaunclassified